1997
DOI: 10.1007/s004010050609
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in the brain transfer of blood-borne horseradish peroxidase in the hippocampus of senescence-accelerated mouse

Abstract: Age-related changes in the brain transfer of blood-borne horseradish peroxidase (HRP) were examined by light microscopy in senescence-accelerated prone mice (SAMP8) and senescence-accelerated resistant mice (SAMR1). The intracerebral HRP transferred from the blood stream was reacted with tetramethyl benzidine (TMB) and the area showing the presence of HRP-TMB reaction products was morphometrically evaluated. Areas containing HRP reaction products in the medial CA1 region and medial dentate gyrus of the hippoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 34 publications
2
39
0
Order By: Relevance
“…SAMR mice with normal characteristics of aging consist of SAMR1, R2, and R4 strains with a relatively strain-specific pathological phenotype. 23) SAMR1 mice show normal aging process. SAMP8 mice have been reported to accumulate Aβ in the brain, where it forms senile plaques.…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations
“…SAMR mice with normal characteristics of aging consist of SAMR1, R2, and R4 strains with a relatively strain-specific pathological phenotype. 23) SAMR1 mice show normal aging process. SAMP8 mice have been reported to accumulate Aβ in the brain, where it forms senile plaques.…”
Section: )mentioning
confidence: 99%
“…Thus, we quantified the accumulation of Aβ40. A standard peptide and the samples were incubated in microplates coated with the monoclonal antibody BNT77, which recognizes human and rat Aβ (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28), for 1 h at 4°C. After washing five times, the plates were incubated with an HRP-conjugated antibody raised against the C-terminus of Aβ40 for 1 h at 4°C.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…28 More bloodborne HRP was transferred in the hippocampus of aged SAMP8 than in the hippocampus of young SAMP8. 31 Ultrastructural examination revealed that uncontrolled passage of HRP in the parajunctional cytoplasm of the endothelial cells was seen in the hippocampus of aged SAMP8, while transendothelial passage of HRP in the basement membrane of vessels in the hippocampus was not found even in aged SAMP8. 29 In addition, ultrastructural features showing BBB damage and immunoreactivity for serum albumin within the basal lamina were seen in the olfactory bulbs of aged SAMP8.…”
Section: Bbb Damage In Experimental Animal Models For Vascular Dementiamentioning
confidence: 99%
“…Thus, earthenware pipe-like subpial medial necrosis and medullary arteriolosclerosis accompanying diffuse white matter lesions in vascular cognitive impairment/Binswanger disease brains appear. 8,9 Moreover, blood-brain barrier alters with aging and even in some normal brain structures such as the olfactory bulb, hippocampus and periventricular areas, [10][11][12] and bloodbrain barrier dysfunctions with the development of capillary collagenosis have been revealed not only in Binswanger disease brains, 13,14 but also spontaneously hypertensive rats and a rat model of chronic cerebral hypoperfusion. 15,16 Recently, it has been shown that the intra-cranial capillary diameter is regulated by pericyte contraction under noradrenergic and purinergic neurotransmitter influences.…”
mentioning
confidence: 99%